Therapeutic processes for communication disorders : a guide for clinicians and students - Fourie, Robert J. (Psychology Press, 2011)
Why do many people with disorders of communication experience a sense of demoralization? Do these subjective experiences have any bearing on how such problems should be treated? How can professionals dealing with speech, language, hearing and other communication disorders analyse and respond to the subjective and relational needs of clients with such problems? In this book, authors in the fields of communication disorders analyse the psychological, social and linguistic processes and interactions that underpin clinical practice, from both client and clinician perspectives. The.